2021
DOI: 10.18196/afkaruna.v17i2.12671
|View full text |Cite
|
Sign up to set email alerts
|

Da'wa in Social Media: The Views of Ustad Hanan Attaki and Felix Siauw to The Hijrah Phenomenon

Abstract: This article examines the views of Ustad Hanan Attaki (UHA) and Ustad Felix Siauw, who use social media as a medium of preaching. The utilization of the internet as a new way of preaching Islam has helped shape contemporary forms of religious thinking and behavior for Muslim youth in Indonesia. One of them is marked by the emergence of the trend of hijrah in their community. This study aimed to explain the Islamic views of UHA and Siauw, which have implications for the emergence and development of the hijrah t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…In February 2019, the Center for Religious and Cultural Studies (CSRC) of the Syarif Hidayatullah State Islamic University (UIN) Jakarta showed that millennial Muslims considered da'wah or studies in mosques longer relevant to their problems. UIN Jakarta's findings published in a book entitled 'Masjids in the Millennial Era: A New Direction of Religious Literacy' stated that young people are no longer interested in the content of da'wah delivered in mosques (Muthohirin, 2021).…”
Section: Digital Da'wah Unites Homemakersmentioning
confidence: 99%
“…In February 2019, the Center for Religious and Cultural Studies (CSRC) of the Syarif Hidayatullah State Islamic University (UIN) Jakarta showed that millennial Muslims considered da'wah or studies in mosques longer relevant to their problems. UIN Jakarta's findings published in a book entitled 'Masjids in the Millennial Era: A New Direction of Religious Literacy' stated that young people are no longer interested in the content of da'wah delivered in mosques (Muthohirin, 2021).…”
Section: Digital Da'wah Unites Homemakersmentioning
confidence: 99%
“…Therefore, Ideological Salafis try to eliminate public opinion which considers them to be part of terrorist groups and radical Islam through the transformation of their da'wah movement. The Salafi transformation is carried out in two mainstream movements, namely: First, the transformation of Salafi Islamic educational institutions, by integrating the curriculum of the Imam Ibn Sa'ud Islamic University in Saudi Arabia and the national education curriculum; Second, dissemination of the hijrah narrative to young Muslims in Indonesia, both online and offline (Akmaliyah, 2020;Hew, 2018;Muthohirin, 2021). This research is only limited to the transformation of Salafis in the field of Islamic education after the increasing suspicion of it as a group that disseminates the ideas of Wahhabism and is affiliated with terrorism globally.…”
Section: Salafi Madrasas Transformationmentioning
confidence: 99%
“…Also, the preaching method has fulfilled the three methods in Surah An-Nahl verse 125: the Al-Hikmah method, Al-Mauidzatu-l Hasanah, and Wa-Jadilhum Bi Al-Lati Hiya Ahsan (Parhan et al, 2020). Next, he focused on hijrah, a message of Islamic da'wa that not only tells about individual repentance but also as a current trend that young Muslims must follow (Muthohirin, 2021).…”
Section: Table 3 Percentage Of Inspirational Preachersmentioning
confidence: 99%